Digital Ionospheric Sounding in Support of Arctic Research. - Bibl,Klaus; Reinisch,Bodo W.; Smith,Sheryl (1976)
Digital acquisition of ionospheric data in arctic regions was carried out by two Digisondes, one in Goose Bay, Labrador, the other aboard AFCRL'S KC-135 aircraft. New digital display methods were incorporated in these systems. The hourly ionograms from Goose Bay for March 1974 to February 1975 were reduced and monthly median curves presented. Development of a new Automatic Ionogram Reduction (AIR6) computer program reduced data storage requirements by a factor of 10. Up to six echoes, two in the E-region and four in the F-region, are detected for each frequency in the ionogram. Amplitudes, heights and echo spread are retrieved together with the noise for each frequency. A pulse matching technique increases the height accuracy by a factor of three compared to the original digital ionogram. For on-line operation a hardware system, the AIC6, was designed using micro-processor techniques.